(untitled) (Qualitative Research Journal for Social Studies, 2025)
The preservation of religious heritage represents a fundamental responsibility of modern nation-states, particularly in societies characterized by cultural diversity and historical pluralism. Pakistan, despite being a predominantly Muslim country, hosts numerous sacred sites belonging to minority communities, including the Sikh religious heritage associated with the life and teachings of Guru Nanak. This article critically examines the role of the Pakistani state in safeguarding Sikh religious heritage through institutional frameworks, administrative policies, and security mechanisms. The study focuses on the preservation and management of gurdwaras located across Pakistan, particularly those situated in Punjab, where the majority of Sikh historical sites are located. Historical records indicate that Pakistan contains hundreds of Sikh religious shrines, many of which date back to the early Sikh Gurus and the Sikh Empire period. According to archival data, more than 588 gurdwaras were recorded in Pakistan, with the majority located in Punjab and Khyber Pakhtunkhwa (Government of Pakistan, 2008). Through qualitative analysis, the article explores how state institutions such as the Evacuee Trust Property Board, provincial administrations, and security agencies collaborate to preserve these heritage sites and facilitate international Sikh pilgrimage. The findings suggest that Pakistan has adopted a relatively structured institutional framework for the preservation of Sikh religious heritage, combining heritage conservation, religious tourism management, and comprehensive security arrangements for visiting pilgrims.